Developmental Psychology and Healthcare Professions: Autism Knowledge Among Nurses: An Observational Study - Rosaria Ferrara; Giuseppe Campagna; Pasquale Ricci; Felice Damato; Lidia Ricci; Leonardo Iovino; Flavio Marti; Roberto Latina; Roberta Simeoli (Clinics and Practice)
Background: One of the biggest limitations faced by autistic people is the lack of knowledge of their condition. Our study aims to evaluate and discuss the knowledge of autism among nurses, which is a social and health category often in close contact with autistic people. Objective: Given the limited exploration of awareness levels about autism among healthcare professionals, this study aims to investigate general and specific knowledge of autism within a group of nursing students enrolled in a master’s degree. Methods: A total of 66 nurses completed the questionnaire. Descriptive analyses were conducted on the results for the four subcomponents of the questionnaire: (i) general knowledge, (ii) symptomatology, (iii) screening and diagnosis, and (iv) intervention and treatment. A correlation analysis was performed between the participants’ demographic variables and questionnaire scores. Additionally, a multivariable logistic regression was conducted to analyze the association between the participants’ basic demographic characteristics and questionnaire scores. Results: Results showed a good percentage of correct answers in the “general knowledge” category. Furthermore, a good level of knowledge regarding the fact that ASD is a developmental disorder and a congenital disease also emerged. Conclusions: Regarding the knowledge of typical autism symptoms, participants answered most of the questions correctly. Correct answers decreased for questions related to screening and diagnosis. In particular, participants had limited knowledge of the DSM-5 and the timing of ASD diagnosis. Similar levels of knowledge were observed for the fourth category, “intervention and treatment”.